Supercharging Node.js applications with Sequelize : create high-quality Node.js apps effortlessly while interacting with your SQL database - Durante, Daniel (Packt Publishing Ltd., 2022)
Continuous changes in business requirements can make it difficult for programmers to organize business logic into database models, which turns out to be an expensive operation as changes to the database may result in errors and incongruity within applications. Supercharging Node.js Applications with Sequelize helps you get to grips with Sequelize, a reliable ORM that enables you to alleviate these issues in your database and applications. With Sequelize, you'll no longer need to store information in flat files or memory. This book takes a hands-on approach to implementation and associated methodologies for your database that will have you up and running in no time. You'll learn how to configure Sequelize for your Node.js application properly, develop a better sense of understanding of how this ORM works, and find out how to manage your database from Node.js using Sequelize. Finally, you'll be able to use Sequelize as the database driver for building your application from scratch. By the end of this Node.js book, you'll be able to configure, build, store, retrieve, validate, and associate your data from a database to a Node.js application.